Eu3+-doped SiO2–Gd2O3 prepared by the sol–gel process: structural and optical properties - Rocha, Leonardo Alves; Schiavon, Marco Antonio; Ribeiro, Sidney José L. [UNESP]; Gonçalves, Rogéria Rocha; Ferrari, Jefferson Luis (Springer Nature, 2015)
Abstract: Eu3+-doped SiO2–Gd2O3 materials were prepared by the sol–gel process changing the Si4+:Gd3+ molar ratio of 100:0, 70:30, 50:50, 30:70 and 0:100 mol%. The amount of Eu3+ was fixed at 0.2 mol% in relation to the total number of moles of [Si4+ + Gd3+] in the systems. The xerogels obtained from sols were heat-treated at 900, 1000 and 1100 °C for 8 h. By TGA/DTA, XRD and Raman spectroscopy analysis, the formation of Gd2O3 crystalline was detected. The microstrains and crystallite size were calculated by the Williamson-Hall and Scherrer’s equation, respectively. The results showed the direct dependence of microstrain and crystallite size as a function of the heat-treatment temperature. By the FTIR analysis was observed the elimination of species like H2O, O–H and C–H groups, which can act as photoluminescence quenchers. All materials obtained in this work showed intense photoluminescence emission in the red region due to the 5D0 → 7F2 transition of Eu3+. The emission can be observed through the naked eye. The excited state lifetime shows to be dependent on values of refractive index and heat-treatment temperatures. The microstrain values affected the lifetime values and consequently the photoluminescence properties. In summary, the materials obtained in this work showed great absorption in the ultraviolet region promoting intense emission in the visible region, making them potential candidates for future applications in devices such as solar cells, image generator, biomarkers, among others. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Eu3+-based phosphors; Photoluminescence; SiO2–Gd2O3; Sol–gel